2012
DOI: 10.2310/8000.2011.110475
|View full text |Cite
|
Sign up to set email alerts
|

Bedside emergency department ultrasonography availability and use for blunt abdominal trauma in Canadian pediatric centres

Abstract: Objectives: To quantify the current availability and use of bedside emergency department ultrasonography (EDUS) for blunt trauma at Canadian pediatric centres and to identify any perceived barriers to the use of bedside EDUS in such centres. Methods: An electronic survey was sent to 162 pediatric emergency physicians and 12 site directors from the 12 pediatric emergency departments across Canada. Results: Ninety-two percent (11 of 12) of centres completed the survey. The individual physician response rate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…For numerous conditions, compared with other imaging modalities, ultrasound can provide a rapid and accurate diagnosis at lower cost and without radiation exposure [1][2][3][4][5][6][7][8][9][10][11][12]. In addition, the appropriate application of ultrasound in the ED setting can decrease length of stay and improve patient satisfaction [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For numerous conditions, compared with other imaging modalities, ultrasound can provide a rapid and accurate diagnosis at lower cost and without radiation exposure [1][2][3][4][5][6][7][8][9][10][11][12]. In addition, the appropriate application of ultrasound in the ED setting can decrease length of stay and improve patient satisfaction [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…19 The current review proved that the reliability of the FAST technique has dramatically improved with innovations in ultrasound equipment systems. 38 It was concluded that the FAST technique has high sensitivity and specificity in the diagnosis of BAT. 39 However, a large range of sensitivity and specificity of the FAST technique, in the evaluation of torso trauma, reveal that sonography is operator, technique, and equipment dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Although their assessment was focused primarily on the USA, emergency ultrasound (EUS) is a practice that crosses international borders. Bedside EUS is used in nearly half of paediatric trauma centres in Canada, with high usefulness 2. Similarly, healthcare providers in Africa have reported that pulmonary, musculoskeletal and cardiac ultrasound is used frequently 3.…”
Section: Introductionmentioning
confidence: 99%